Pemberian Edukasi Bahaya Radikal Bebas melalui Pengolahan Minuman Kesehatan Lidah Buaya pada Penghuni Rumah Yatim Ar-Rohmah Banjarbaru Kalimantan Selatan - Rahmi Hidayati; Ratna Restapaty; Putri Indah Sayakti (LPPM Universitas Flores, 2021)
Excess free radicals in the body to exceed the body's ability to manage it can cause a condition called oxidative stress. The impact of free radicals can attack and cause damage to various cells of the body. Antioxidants play a very important role for the health of the human body because their function can inhibit and neutralize the occurrence of oxidation reactions involving free radicals (Parwata, 2016). Antioxidants in food or beverages can contain natural antioxidants such as in vegetables, fruits and beverages as well as synthetic antioxidants that are deliberately added to the food and beverages consume. The problem in the orphanage environment becomes a challenge as well as an opportunity to provide education related to the dangers of free radicals and the processing of aloe vera drinks. Method of implementation of activities by providing education on the dangers of free radicals and demo processing aloe vera drink (Aloe Vera). The results of data analysis from questionnaires shared with orphaned residents showed that as many as 94.7% of people who had never followed counseling about the dangers of free radicals and aloe vera drink processing. Although many benefits are obtained from aloe vera, but the level of public consumption of aloe vera is very minimal, especially in the form of drinks. Processed products from aloe vera in the form of drinks containing antioxidants as a neutralizer of free radicals is very good, because beverage products are easier to digest by the body and the content in aloe vera (Aloe Vera) is still natural because it has not undergone many treatments. In addition, it is recommended to change high-risk habits and reduce the danger of free radicals by; 1) avoid being under UV light directly, 2) avoid excessive radiation from electronic devices, 3) avoid foods that are burned, smoked and fried excessively.